2015
DOI: 10.1051/0004-6361/201526043
|View full text |Cite
|
Sign up to set email alerts
|

Angular momentum redistribution by mixed modes in evolved low-mass stars

Abstract: The detection of mixed modes in subgiants and red giants by the CoRoT and Kepler space-borne missions allows us to investigate the internal structure of evolved low-mass stars, from the end of the main sequence to the central helium-burning phase. In particular, the measurement of the mean core rotation rate as a function of the evolution places stringent constraints on the physical mechanisms responsible for the angular momentum redistribution in stars. It showed that the current stellar evolution codes inclu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 48 publications
0
49
0
Order By: Relevance
“…The internal rotation rates of red giants, as measured by asteroseismology, is a few orders of magnitude smaller than what is predicted by rotating stellar models (Mosser et al 2012), indicating that one or several missing angular momentum transport processes are at work in these evolved stars (e.g. Fuller et al 2014;Rüdiger et al 2015;Belkacem et al 2015;Eggenberger et al 2017).…”
Section: Introductionmentioning
confidence: 83%
“…The internal rotation rates of red giants, as measured by asteroseismology, is a few orders of magnitude smaller than what is predicted by rotating stellar models (Mosser et al 2012), indicating that one or several missing angular momentum transport processes are at work in these evolved stars (e.g. Fuller et al 2014;Rüdiger et al 2015;Belkacem et al 2015;Eggenberger et al 2017).…”
Section: Introductionmentioning
confidence: 83%
“…Other studies show that additional mixing is needed to explain observed rotation profiles of red giants or subgiants Ceillier et al 2012;Marques et al 2013). Moreover, even adding other transport processes is still not sufficient to explain the observations , for the Tayler-Spruit dynamo; Fuller et al 2014;Belkacem et al 2015, for internal gravity waves). Constraints from the spin of neutron stars and white dwarfs at birth also indicate that the transport as predicted by Zahn's model is not sufficient (Heger et al 2005, for neutron stars; Suijs et al 2008, for white dwarfs).…”
Section: Introductionmentioning
confidence: 93%
“…for a benchmark model. In a companion paper (Belkacem et al 2015, hereafter Paper II) we consider realistic mode amplitudes to quantitatively estimate the efficiency of the angular momentum transport by modes along the evolution of low-mass stars. This paper is organised as follows: Sect.…”
Section: Introductionmentioning
confidence: 99%